2013
DOI: 10.1111/azo.12039
|View full text |Cite
|
Sign up to set email alerts
|

Gain of palps within a lineage of ancestrally burrowing annelids (Scalibregmatidae)

Abstract: Scalibregmatidae is a small annelid family of subsurface deposit feeders in sand or mud, which are generally well adapted to infaunal burrowing. The overall morphology of Scalibregmatidae is very similar, with thick bodies, small parapodia, and no prostomial appendages or short horns. The only exception is members of the genera Axiokebuita and Speleobregma that most frequently inhabit crevices or gravel and possess extensive ventral ciliated palps and globular adhesive pygidium. Character reconstruction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
(159 reference statements)
0
11
0
Order By: Relevance
“…; Martínez et al . )). However, we modified this method, following Wright & Hillis () to set the parameter that defines character change by randomly drawing from a gamma distribution (with a shape parameter of 0.5 and a rate parameter of 5) for each character within the matrix.…”
Section: Methodsmentioning
confidence: 94%
“…; Martínez et al . )). However, we modified this method, following Wright & Hillis () to set the parameter that defines character change by randomly drawing from a gamma distribution (with a shape parameter of 0.5 and a rate parameter of 5) for each character within the matrix.…”
Section: Methodsmentioning
confidence: 94%
“…). In comparison, other non‐scale worm annelids inhabiting caves are non‐predatory and exhibit elongated palps, serving both in sensing and in capturing suspended organic particles from the water column (Martínez et al., ; Worsaae et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Four independent analyses, with four chains (three heated and one cold), were run for 30 million generations. For each Bayesian Markov chain, three hundred trees were obtained by sampling at intervals of 20k generations, ensuring statistical independence of the samples (Martínez, Di Domenico, & Worsaae, ; Pagel, Meade, & Barker, ). Burn‐in was set to 10 million generations.…”
Section: Methodsmentioning
confidence: 99%
“…However, a small group of scalibregmatids of the genera Axiokebuita and Speleobregma have very elongate horns that are ciliated and with shallow grooves that suggest they function to support feeding rather than burrowing (Parapar et al 2011;Martínez et al (2013Martínez et al ( , 2014 and have been termed 'palps." Use of these "palps" in feeding was confirmed for two marine cave-dwelling species of these genera that inhabit coarse sediments rather than the soft muddy sediment habitat typical of most scalibregmatids (Martínez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This character is an additional aspect of the overall morphology of scalibregmatids that deserves further study. The recent papers by Parapar et al (2011b) and Martínez et al (2013Martínez et al ( , 2014 on two closely related scalibregmatid genera, Axiokebuita and Speleobregma, suggest that a ventral groove or ridge line is completely absent in all described species of these two genera. If so, then, in conjunction with the complete absence of lyrate setae, acicular spines, branchiae, and parapodial cirri, together with the presence of an unusual prostomium with long ciliated lateral horns (termed palps by these authors) and an unusual peristomial sensory structure, this clade as reported by these authors differs considerably from other scalibregmatids.…”
Section: Discussionmentioning
confidence: 99%